ANALYSIS OF CELEBRITY ENDORSEMENTS IN SOCIAL MEDIA ON CONSUMER SATISFACTION THROUGH PURCHASE DECISIONS FOR SCARLETT WHITENING PRODUCTS (CASE STUDY IN BEKASI CITY) - Laras Meidiarti; Hadita Hadita (Dinasti Publisher, 2022)
The purpose of this study was to determine the effect of the Celebrity Endorsement promotion strategy on social media used by the Scralett Whitening brand on consumer satisfaction through purchasing decisions. In this study using quantitative research methods and in obtaining a sample the author uses the Purposive Sampling method. The number of samples used in this study were 144 respondents, where the focus of this respondent was the Scarlett Whitening consumer. The results of the research that has been done there are variables that influence each other and some do not, as in the following brief explanation: 1). In the Celebrity Endorsement variable on Consumer Satisfaction there is a positive and significant influence with the value of T_Statistics 2,329 > T_table 1, 96. 2) In the Celebrity Endorsement variable on the Purchase Decision, there is a positive and significant effect with the T_Statistic value of 6.376 > T_table 1.96. 3) The Purchase Decision variable on Consumer Satisfaction is stated to have a positive and significant effect with a T_Statistic value of 6.134 > T_table 1.96. 4) The indirect effect of the Celebrity Endorsement variable on Consumer Satisfaction through the Purchasing Decision variable is proven to be significant and is declared fully mediated with the value of T_Statistic 4.494 > T_table 1.96.